The Product Involvement Effect on Thought Elicitation and Attitude Strength in The Online Environment - Palla, Polyxeni Jenny; Kyriacou, Evdoxia; Zarkada, Anna K. (My University, 2022)
The online attitude formation process has become a critical issue not only for academics but also for practitioners. An emerging question is whether the level of product involvement acts as a moderating variable in online attitude formation and attitude strength. The current work seeks to examine whether the level of product involvement presented in a website acts as a moderator on thought elicitation and attitude strength. The Elaboration Likelihood Model (ELM) is utilized to support the experimental design. The results of this survey have provided some initial insights into attitude formation and attitude strength towards the brand.
Keywords: Online advertising; Thought elicitation; Attitude strength; ELM; Persuasive communication